High altitude pulmonary hypertension: pathogenesis and disease management - Diaz-Lazo, Anibal Valentin (2022)
The purpose of this article is to review the pathogenesis and management of altitude pulmonary hypertension (APH), which is a disease resulting from chronic exposure to altitude and, at present, it is not defined whether it is a public health problem or a rare disease. The prevalence of APH varies according to geographic, environmental and genetic location. The population living at high altitude is chronically exposed to alveolar hypoxia; this causes vasoconstriction and then pulmonary vascular remodeling. APH is usually asymptomatic; only in advanced stages does it produce symptoms characterized by exertional dyspnea and fatigue. The accurate diagnosis is right heart catheterization with mean arterial pressure values greater than 30 mmHg or systolic pulmonary artery pressure greater than 50 mmHg. The ideal treatment is the descent of the patient to low places. Prognosis is good in most cases.